Clinical course of sly syndrome (mucopolysaccharidosis type VII). Issue 6 (23rd February 2016) - Montaño, Adriana M; Lock-Hock, Ngu; Steiner, Robert D; Graham, Brett H; Szlago, Marina; Greenstein, Robert; Pineda, Mercedes; Gonzalez-Meneses, Antonio; Çoker, Mahmut; Bartholomew, Dennis; Sands, Mark S; Wang, Raymond; et al.
Abstract : Background: Mucopolysaccharidosis VII (MPS VII) is an ultra-rare disease characterised by the deficiency of β-glucuronidase (GUS). Patients' phenotypes vary from severe forms with hydrops fetalis, skeletal dysplasia and mental retardation to milder forms with fewer manifestations and mild skeletal abnormalities. Accurate assessments on the frequency and clinical characteristics of the disease have been scarce. The aim of this study was to collect such data. Methods: We have conducted a survey of physicians to document the medical history of patients with MPS VII. The survey included anonymous information on patient demographics, family history, mode of diagnosis, age of onset, signs and symptoms, severity, management, clinical features and natural progression of the disease. Results: We collected information on 56 patients from 11 countries. Patients with MPS VII were classified based on their phenotype into three different groups: (1) neonatal non-immune hydrops fetalis (NIHF) (n=10), (2) Infantile or adolescent form with history of hydrops fetalis (n=13) and (3) Infantile or adolescent form without known hydrops fetalis (n=33). Thirteen patients with MPS VII who had the infantile form with history of hydrops fetalis and survived childhood, had a wide range of clinical manifestations from mild to severe. Five patients underwent bone marrow transplantation and one patient underwent enzyme replacement therapy with recombinant human GUS. Conclusions: MPS VII is a pan-ethnic inherited lysosomal storage disease with considerable phenotypical heterogeneity. Most patients have short stature, skeletal dysplasia, hepatosplenomegaly, hernias, cardiac involvement, pulmonary insufficiency and cognitive impairment. In these respects it resembles MPS I and MPS II. In MPS VII, however, one unique and distinguishing clinical feature is the unexpectedly high proportion of patients (41%) that had a history of NIHF. Presence of NIHF does not, by itself, predict the eventual severity of the clinical course, if the patient survives infancy.